EFFECT OF PREMORBID FACTORS ON THE CLINICAL COURSE OF COMMUNITY-ACQUIRED PNEUMONIA IN CHILDREN - Дорохов, Николай Алексеевич; Скударнов, Евгений Васильевич; Антропов, Денис Александрович; Бойко, Андрей Владимирович; Даулетова, Янина Анатольевна (Mother and Baby in Kuzbass, 2017)
Pulmonary-pleural complications in children with pneumonia occur at different stages of the disease, which necessitates the analysis of predisposing and premorbid factors that affect the risk of developing complications of pneumonia in children.Objective. To identify and analyze predisposing and premorbid factors in children with complicated and uncomplicated pneumonia, as well as to assess their impact on the severity of the inflammatory process.Materials and methods. All patients were conducted: 1) collection of complaints, anamnesis (morbi, vitae, all mothers were collected gynecological, obstetric history, data of pregnancy and delivery); 2) physical examination; 3) complete blood count (white blood cells, blood count, erythrocyte sedimentation rate, hemoglobin, color index, platelet count); 4) biochemical analysis of blood; 5) chest X-ray. The work has been used by the International Classification of Diseases Tenth Revision (1992).Results. The study was divided into two groups of patients: the first group included children with a diagnosis of uncomplicated pneumonia (n = 61), which accounted for 38 % of the patients examined. The second group included 100 patients who had pneumonia occurs with pulmonary pleural complications, which amounted to 62 % of the total number of patients studied. Children with pneumonia in the presence of predisposing and premorbid factors such as: late access to a doctor; low or unfavorable social conditions; availability (perinatal pathology) maternal pregnancy pathology, extragenital pathology; Early replacement feeding; the presence of a child background diseases, atopy; signs of iron deficiency (according to full blood count) may be attributed to the risk of developing lung, pleural complications.Conclusion. All the factors have an impact on the severity of inflammation in the lung. Influence of these factors previously noted in the risk of fatal pneumonia in children.
Keywords: children; pneumonia; complication; premorbid factors